Filsafat Ilmu sebagai Fondasi Pengembangan Ilmu Pengetahuan Modern dalam Perspektif Pendidikan Islam - Ibtihal Istiqomah; Siti Fatimah (An-Nuha, 2026)
This study aims to analyze the role of the philosophy of science as a foundation for development of modern science through ontological, epistemological, and axiological perspectives, and to examine its relevance in addressing contemporary challenges. This research employs a qualitative approach using a literature review of scientific sources. The findings show that the philosophy of science plays an essential role in explaining the nature of scientific objects, the validity of knowledge acquisition, and the ethical use of knowledge. Amid rapid scientific and technological advancements, issues such as moral crises, misuse of technology, and low value awareness have emerged. The novelty of this study lies in integrating the three dimensions of the philosophy of science within contemporary challenges and linking them to the perspective of Islamic education. The study concludes that the philosophy of science serves as both a theoretical foundation and an ethical guide for developing responsible and beneficial knowledge.